Digital economy and private donation behavior: an empirical analysis based on the CFPS data - Li, Xinrong; Shi, Yupeng; Tang, Tianyu (Frontiers in Environmental Science, 2023)
With the development of digital economy, especially the Mobile payment, the lifestyles such as the private donation, is undergoing accelerated changes in the last decades. Based on the China Family Panel Studies (CFPS)2018 data, this paper systematically investigated the donation models, empowered by digital technology, have realized economy system refinement and intelligent development. Compared with residents who do not use the Internet, residents who use the Internet are about 11% more likely to donate, and the amount of donations will increase by about 57%. After considering the potential endogeneity problem, results still hold with Propensity Score Matching (PSM) and Instrumental Variable. The mechanism analysis shows that the searching cost, information asymmetry, and moral hazard play an important role. The research of this paper has enlightening that the widespread use of digital technologies can effectively change the private donation behavior and penetrate energy consumption via dramatically decreasing searching cost.